Bridging TAM and e-Puskesmas: Measuring Perceived Ease of Use in Digital Health - Ciptaningtyas, Ratri; Elia Hamda Humairo; Riastuti Kusumawardani; Fajar Ariyanti; Catur Rosidati (CV. Media Digital Publikasi Indonesia, 2024)
e-Puskesmas is an information system based on data and communication innovation in giving wellbeing administrations which is essential for the benefit of both patients and health care providers. However, the use of e-Puskesmas is still a challenge because some Puskesmas officers have difficulty in using e-Puskesmas. E-Puskesmas was introduced in 2016 and began to be used in Bekasi City Puskesmas in 2019. This study aimed to determine the intensity of e-Puskesmas use as reviewed from sociodemographic and user perception perspectives using the Technology Acceptance Model (TAM) concept. This study was a quantitative research with a cross-sectional design. The sampling method used was multistage random sampling, with a sample consisting of 214 health center officers from five health centers. The research instrument used was a Google Forms questionnaire. The data obtained were statistically tested using the chi-square test. The results showed that sociodemographic factors had a significant relationship with the intensity of e-Puskesmas use. In addition, there was a significant relationship between the perceived usefulness variable (0.018), perceived ease of use (0.014), and intensity of e-Puskesmas use.